2000
DOI: 10.2114/jpa.19.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistive Knee Extension Training on Postural Control Measures in Middle Aged and Elderly Persons.

Abstract: The purpose of the present study was to determine whether knee extension strength gain in middle-aged and elderly persons is associated with improvement in the limits of stability when leaning his/ her body in various directions. The resistance training group (EXT; 4 males, 17 females) completed two bilateral knee extension training sessions, consisting of one set of exercises, per week for 10 weeks. The non-training control group (CONT; 4 males, 3 females) were instructed not to train their legs during the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 23 publications
3
13
0
3
Order By: Relevance
“…Furthermore, there were significant improvements in 8-fit upand-go, which is a demonstration of agility/dynamic balance that is related with lower limb muscle strength (23). In fact, Ryushi et al (24) demonstrated that better balance was due to rises in muscular strength in older adults. Thus, it seems reasonable to believe that these Thai elderly adults significantly improved the performance of tasks dependent on muscle strength (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there were significant improvements in 8-fit upand-go, which is a demonstration of agility/dynamic balance that is related with lower limb muscle strength (23). In fact, Ryushi et al (24) demonstrated that better balance was due to rises in muscular strength in older adults. Thus, it seems reasonable to believe that these Thai elderly adults significantly improved the performance of tasks dependent on muscle strength (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Probably, these agility/dynamic balance improvements might be related to increased muscular strength observed during the training period. In fact, Ryushi et al [36] demonstrated that better balance was due to rises in muscular strength in older adults. Additionally, specific balance activities used in the present study may possibly have stimulated additional benefits [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate strength training may have a positive effect on maximal strength (14,15), muscle size (16,17), muscle architecture (18) and the control of muscular contraction force (14)(15)(16)(17)(18)(19)(20). Another function that is often observed to improve with resistance training is postural stability (21,22). In addition to strength exercises, muscle stretching exercises are also used in conventional physical therapy (23).…”
Section: Introductionmentioning
confidence: 99%